Penilaian Tata Kelola Sistem Drainase Berbasis Prinsip-Prinsip OECD Water Governance - Kusumadewi, Adlina; Adi, Henny Pratiwi; Wahyudi, Slamet Imam (Department of Civil Engineering, Diponegoro University, 2025)
Urban drainage systems play a critical role in managing excess water to prevent flooding, yet challenges such as rapid urbanization, land-use changes, and climate change exacerbate these issues. In Semarang, factors like clogged channels, sedimentation, land subsidence, and tidal flooding further complicate drainage management. The Organisation for Economic Co‑Operation and Development (OECD) Water Governance approach, with its emphasis on effectiveness, efficiency, and stakeholder engagement, provides a promising framework for improving water governance. However, its application in Indonesia, particularly in Semarang, remains underexplored. This study evaluates the implementation of OECD Water Governance principles in managing the Tenggang River drainage system to promote sustainable water governance. Using the OECD Water Governance Indicator Framework, the research assesses the application of 12 principles through a combination of literature review, questionnaires, and interviews with government officials and community representatives. A descriptive analysis supported by interview findings reveals that the principles are moderately well implemented, though discrepancies exist between government and community evaluations. Government respondents provided higher scores for the dimensions of effectiveness (4.70), efficiency (4.73), and trust & engagement (4.88), compared to the community’s scores of 4.30, 4.07, and 4.40, respectively. Nonetheless, both groups rated the trust & engagement dimension the highest among all.